Sustained release of drugs from prepared polymeric systems for Alzheimer disease protection - Doaa E El-Nashar (Journal of Global Pharma Technology, 2020)
Objective: Slow release technique is a trial for long-acting protection from Alzheimer. Drug delivery systems, polymer based, can be designed to improve the pharmacological and therapeutic properties. Slow release technique gave the availability of drugs to deliver the right location in the body. The main principle of this technique is holding and keeping the drug on the polymer carrier for a sustained release of medicine in the body for a long period of time. The present work aimed to prepare polymeric materials from starch cellulose acetate coacrylate (SCACA), containing sodium bentonite nano clay and tween 80 as a surfactant for improving drug loading. The objective of this formulated natural polymeric product is to obtain practical effective sustained release drug systems by evaluating its potency in vivo for protection from Alzheimer disease. SCACA biodegradable polymeric system formulations containing anti Alzheimer drugs (such as Curcumin, Rosemary or Donepezil) were investigated through oral administration in experimental animals (rats). Methods: The characterization of the prepared polymeric system was carried out by FTIR and SEM. The drug release was measured spectrophotometrically. The invivo evaluation of the released drug against Alzheimer disease was an assessment of the effect in rats through biochemical and histopathological studies. Results: The slow release of the drug according to the study time illustrated that Rosemary, Curcumin and Donepezil estimated values through the tested time gave promising results, especially for releasing Rosemary, Curcumin and Donepezil. In the present investigation, the biochemical findings were also confirmed by histopathological observations which showed improvements in most biochemical parameters accompanied with amelioration in histological architectures in rats treated. Conclusions: Slow release technique is a good means for long-acting protection from Alzheimer's disease. Starch cellulose acetate coacrylate (SCACOA) is a good carrier for drugs such as Donepezil as a conventional drug while Rosemary, Curcumin as bioactive natural products. The invivo study for Alzheimer's protection gave promising results.